2019
DOI: 10.1186/s40529-019-0259-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and expression of sesquiterpene pathway genes responsible for patchoulol biosynthesis and regulation in Pogostemon cablin

Abstract: Background Many commercially important drug and flavor compounds are secondary metabolites of terpenoid origin. Pogostemon cablin , a commercially important industrial and medicinal crop, accumulates abundant patchouli oil comprised of more than 24 unique sesquiterpene compounds, with the most abundant being patchouli alcohol. Results In this study, we analyzed the P. cablin transcriptome library, obtaining 74 terpen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…The reaction mechanism of (−)‐patchoulol formation by the PTS has not yet been clarified in detail . More particularly, there is no proof in the literature on further reprotonation steps as postulated by Faraldos et al Because the formation of PTS products is obviously influenced by the pH‐value, it is possible that protons from the reaction solution are directly involved in the mechanism of terpene formation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reaction mechanism of (−)‐patchoulol formation by the PTS has not yet been clarified in detail . More particularly, there is no proof in the literature on further reprotonation steps as postulated by Faraldos et al Because the formation of PTS products is obviously influenced by the pH‐value, it is possible that protons from the reaction solution are directly involved in the mechanism of terpene formation.…”
Section: Resultsmentioning
confidence: 99%
“…Optimization of pH during bioconversion was tested by measuring product ratio with optimal activity buffer (50 mM MES, 10 mM MgCl 2 , 10% (v/v) glycerol) at pH 5.6, 5.8, 6.0, 6.2, 6.4, and 6.6 and 38 C. After evaluation of optimal pH, the biotransformation was analyzed for optimal temperature with optimal activity buffer (50 mM MES, 10 mM MgCl 2 , 10% (v/v) glycerol, pH 6.4) at 30,32,34,36,38,40,42, and 44 C. For each measuring point a glass vial was filled with activity buffer, substrate (FPP = 30 μM) and 0.5 μM enzyme to a total volume of 500 μl, overlaid with 150 μl of isooctane and incubated for 10 min in a water bath. After stopping reaction by shaking for 30 s, reaction volume was centrifuged, 80 μl of the organic phase was transferred to a GC vial and measured in GC-FID (see…”
Section: Temperature and Ph Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“… Chen et al (2020) found that overexpression of PatMYB46 in P. cablin could increase the content of PA. Li et al (2021) found that overexpression of PatGT-1 in P. cablin could reduce the content of PA and revealed that PatGT-1 negatively regulates PA biosynthesis. Recently, the molecular dynamics of P. cablin have been gradually revealed, especially the genes controlling the synthesis of PA ( Tang et al, 2019 ). However, there is limited information on the regulation of its TFs to date, especially PA biosynthesis in P. cablin .…”
Section: Discussionmentioning
confidence: 99%
“…Patchouli alcohol, a natural tricyclic sesquiterpene compound that is a bioactive ingredient in P. cablin [21], is used worldwide in decorative cosmetics, toilet soaps, perfume industries [22] and medical treatments [23]. With the increasing market demand in the world, a metabolic engineering approach has been considered an effective approach to increase useful metabolites in medical plants, and several strategies have been reported to promote the industrialization process of patchouli alcohol production using Saccharomyces cerevisiae [24], and gene isolation and cloning in MVA and MEP pathways participating in patchouli alcohol biosynthesis have been reported [25]. In addition, full-length transcriptome data reported provide a valuable genetic resource in P. cablin [18].…”
Section: Discussionmentioning
confidence: 99%